Entrepreneurial ecosystem of small medium industries (SMEs): a preliminary study in Malaysia - Wan Yusoff, Wan Fauziah (IBIMA, 2016)
Small Medium Enterprises (SMEs) particularly those from emerging countries presence significant roles to the economic development. Despite of their constraints, SMEs are struggling to expand into the international market and compete internationally. This study aims to explore the SMEs from emerging countries by examining the ecosystem of the SMEs in Malaysia. Based on qualitative methods specifically personal interviews using open ended questionnaire involving 35 SMEs’ owners, the study discovered that the development of entrepreneurial ecosystem of Malaysia required all the six elements; finance, market, human capital, business culture, business support and policy. Nevertheless, the importance of the six components slightly differ from Iceberg Model (2010). Although the Iceberg model stated policy as the first or the most important component of the entrepreneurial ecosystem, in Malaysia the SMEs have emphasized more on the importance of finance and market. . As the majority of Malaysian SMEs are still smaller and operate locally, they need more market and financial resource to expend their business globally. This study provide basic information for future research of the entrepreneurial ecosystem development for the enhancement of SMEs Masterplan 2012-2020.